Control de biofilm y prevalencia de caries en adultos consumidores de bebidas con stevia - Basantes Andino, Ivonne Pamela (2017)
The most common oral infectious disease is the dental cavities, this is considered polymicrobial. The dental cavity is a destroying process, where dental tissues are affected, it could be necrosis if the dental pulp is damaged and after that the support bone tissues are affected. The main cause of the dental cavity is the sucrose that is why the natural sweeteners were created for preventing of them. Nowadays, the natural sweeteners are consumed by idiosyncrasy of the society. The sucrose is the factor why the biofilm could add easily, at the same time produce cavities. The fermentation of bacteria generates acids and it ended up in demineralization of enamel. The average of dental cavities and the biofilm between people who consume Stevia drinks and people who do not, it is the main objective of this present project. I made some questions and the clinical exam over 50 people who are eighteen and up, then twenty-five people belongs to Stevia group and the others twenty-five people belongs to sucrose group.